Ewolucja międzynarodowego rynku finansowego a zarządzanie finansami firm - przyczynek do dyskusji - Dziawgo, Danuta (International Financial Markets Evolution and Financial Management (in Outline), 2007)
Changes in the resources and structure of financial assets on the international financial markets are already so essential that in consequence they will change the style of financing economic subjects. The model will shift from dominating by banking sector to dominating by securities market (so-called American model). It seems that these changes will influence not only the European but also the Asian market. In effect, the so-called American model will change into a global model. As a consequence the above mentioned process of evolution, subjects should modify their financial management. Especially non-financial companies whose demand for financial capital should consider hat evolution. They should treat capital market as a more and more important source of capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 87-97